2019
DOI: 10.3390/foods8100490
|View full text |Cite
|
Sign up to set email alerts
|

Review on Natural Preservatives for Extending Fish Shelf Life

Abstract: Fish is extremely perishable as a result of rapid microbial growth naturally present in fish or from contamination. Synthetic preservatives are widely used in fish storage to extend shelf life and maintain quality and safety. However, consumer preferences for natural preservatives and concerns about the safety of synthetic preservatives have prompted the food industry to search natural preservatives. Natural preservatives from microorganisms, plants, and animals have been shown potential in replacing the chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
147
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(148 citation statements)
references
References 231 publications
(190 reference statements)
1
147
0
Order By: Relevance
“…A growing number of consumers are aware of the potential negative health effects of chemical preservatives, which has prompted the food industry to find natural products used and developed as alternatives [48]. Concerns about synthetic preservatives have caused increasing interest in natural antioxidants [49].…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of consumers are aware of the potential negative health effects of chemical preservatives, which has prompted the food industry to find natural products used and developed as alternatives [48]. Concerns about synthetic preservatives have caused increasing interest in natural antioxidants [49].…”
Section: Discussionmentioning
confidence: 99%
“…This has forced food processing companies to employ a variety of hurdle procedures in an effort to ensure that their food products are L. monocytogenes -free [ 23 , 24 , 25 ]. Several technologies and intervention strategies aimed at inhibiting or killing these pathogens thereby improving the microbiological quality have been employed albeit with varying levels of success [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…High hydrostatic pressure (HHP), phage biocontrol, bacteriocin-producers, or bioprotective cultures, nisin, sodium chloride, sodium lactate, and other food-grade antimicrobials are some of the treatments and techniques used to increase the safety of RTE food products [ 28 , 29 , 30 , 31 , 32 , 33 , 37 , 38 , 39 , 40 ]. These measures can prolong product shelf life, which is critical due to the globalization of the food industry, as food is often transported over long distances before consumption [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural preservatives generally originate from microorganisms, plants, and animals. Mei et al (2019) suggested that plant extracts might have broad application prospects in the preservation of fish. Numerous in vitro studies have been conducted to evaluate the antioxidant and antimicrobial activities of plant extracts.…”
Section: Introductionmentioning
confidence: 99%